TOWARDS A RESILIENT INDONESIA: EMPOWERING COMMUNITIES THROUGH INCLUSIVE SOCIAL PROTECTION POLICIES - Septian, Esa; Wulandari, Septi (Journal of Social Politics and Governance (JSPG), 2024)
This research aims to examine social protection policies in the context of national economic recovery (PEN) due to the impacts of COVID-19. The pandemic has exacerbated the complexities of poverty, inequality, and unemployment. A qualitative study design is employed, gathering data through a literature review of relevant government documents, journals, and news articles, and utilizing the problem structuring method. The findings indicate that social protection policies have not yet had a significant impact. The implementation of the pre-employment card program faces several challenges, including fund misappropriation and inaccurate data submissions. The research offers several policy alternatives: 1) Addressing limitations imposed by the COVID-19 pandemic; 2) The informal sector, being the most economically affected, requires community business stimulus; 3) Ensuring that social protection policies are fully compliant with legal frameworks; 4) Social and skill enhancement initiatives targeting impoverished populations; and 5) Robust social protection grounded in community empowerment. The originality of this research lies in its emphasis on the critical role of the government in implementing equitable, relevant policies with a significant societal impact and a focus on public interest.